Pengaruh Motivasi Belajar Menggunakan Zoom dan Kecemasan Belajar Terhadap Prestasi Belajar Matematika Siswa Kelas X - Muslihatul Hidayah; Dona Katarina; Iim Marfu’ah (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2022)
The purpose of this study is that there are still many students who do not fully understand the use of zoom so that it affects learning motivation, some students still feel high learning anxiety so that it affects mathematics learning achievement, students who have low learning motivation affect learning achievement through learning anxiety. Furthermore, after the research implementation team conducted observations and interviews with several teachers at SMK N 2 Wonogiri, it was found that some students at the SMK still had difficulties in operating zoom and other similar media and the limited quota even though they received quota assistance but sometimes it was not sufficient. From this background, the research team wanted to investigate further about the effect of learning motivation using zoom and learning anxiety on mathematics learning achievement at SMK Negeri 2 Wonogiri. The method used is a quantitative approach, namely solving path analysis problems with a linear regression approach. The result of this research is that there is an effect of learning motivation using zoom on mathematics learning achievement. There is an influence of learning anxiety on mathematics learning achievement. There is an effect of learning motivation using zoom on mathematics learning achievement through learning anxiety. Keywords: learning motivation, zoom, learning anxiety, mathematics learning achievement